IMPROVEMENT OF ASSET MANAGEMENT BY E-INVENTORY ASSET MANAGEMENT SYSTEM - Buyamin, Syahrunizam; Abdul Hamid, Abdul Hafiz; Ibrahim, Mohd Fairose; Hashim, Noraini (Management Research Journal, 2012)
Searching and recording assets in a laboratory is a critical task. This would occur because data storage would interfere with the search process causing the searching to be slower, without record of stock issuance, loss of badger and involuntary cutting off the supply of assets. Consequently, the E-Inventory Asset Management System was built to manage data storage, updating and facilitating the search for assets. This study was carried out at the workshop at the Department of Electrical Engineering, Politeknik Sultan Azlan Shah in 2011. E-Inventory Asset Management System was built by combining electronic hardware, computer equipment and also Visual Basic 6.0 software. This system can also be applied with the Bar Code Reader. Research on the effectiveness of E-Inventory Asset Management System was implemented and the data analyzed by comparing the time consumption between application of manual system and E-Inventory Asset Management System. The results shown that E-inventory Asset Management System facilitated and accelerated the management searching time on disposable item assets at the Installation and Wiring Workshop, Electrical Engineering Department, Polytechnic Sultan Azlan Shah. In addition, the safety factor on the recording of the loan, and the need to make the order before running out of stock can also be controlled by using E-Inventory Asset Management System. From this study, it can be concluded that the computerization of asset management systems could facilitate searching in terms of asset management, data storage, security and the re-ordering of the stock.